A new religion for the 21st century: an interpretation of ‘dataism’ from the sociology of pierre bourdieu (The Journal of Psychology and Sociology, 2023)
The article makes predictions about dataism, noting disagreements over the definition, highlighting the tendency to perceive it as a problematic threat to humanity. Dataism is considered in terms of spe-cific religious traits, the construction of faith and trust in algorithms, the formation of groups of specialists and the accumulation of symbolic power. Pierre Bourdieu's sociology of religion is a theoretical frame-work used to study worldviews, beliefs, and moral precepts stemming from dataism. In turn, virtuality and digital practices challenge the traditional concepts of habitus and disposition used in sociology, which requires redefining some of the epistemological and methodological aspects of such a conceptual framework. Dataism began as a neutral scientific theory, but now it is mutating into a religion that claims to define right and wrong. Bourdieu's approach to the study of religious phenomena (the composition of the clergy, the distribution of habitus among the population and the relationship between religious and non-religious areas) provides an interpretation of dataism that creates and provides for spiritual needs, a worldview associated with trust in the algorithm and moral requirements arising from the dogma of free-dom information. At the same time, the question is raised of further clarification of the actors involved in the institutionalization of the clergy, about the places and temporality for performing rituals and habitus, about the actions of technological devices. The author supports the conceptualization of dataism as a religion, as it suggests elements that provoke beliefs, doctrines, and practices that are capable of chang-ing society, and shares considerations to guide further theoretical or empirical research into dataism .Key words: Bourdieu, dataism, religion, virtuality, digital practices.